Measuring Maqasid Sharia for Corporate Social Responsibility (The Analysis on Bank Indonesia Scholarship Program) - Ainun Amalia Zuhroh (Jurnal Ilmiah Ekonomi Islam, 2025)
This study aims to determine the practice of Corporate Social Responsibility (CSR) program at Bank Indonesia to optimizing education by scholarship program at University of Darussalam Gontor based on maqasid sharia overview. The method used in this research is field research, which directly related to the object. The data source used in this study are primary and secondary data collected by triangulation method. In the process, researchers conducted observations, interviews with 30 respondence and documentation. The results showed CSR program in the form of scholarships has included the principle of maqashid perspective on the aspect of Tahẓib al-Fardh (Individual Education). In general, the impact of CSR Education for BI scholarship recipients and UNIDA Gontor is a strategic social investment. The recommendation is the application of maqᾱṣid al-shari’ah in the community of Bank Indonesia scholarship recipients must be implemented even better so it can be utilized by students and by the community.